Clinical Characteristics, Treatments and Outcomes of 18 Lung Transplant Recipients with COVID-19 - René Hage; Carolin Steinack; Fiorenza Gautschi; Susan Pfister; Ilhan Inci; Macé M. Schuurmans (Transplantology, 2021)
We report clinical features, treatments and outcomes in 18 lung transplant recipients with laboratory confirmed SARS-CoV-2 infection. We performed a single center, retrospective case series study of lung transplant recipients, who tested positive for SARS-CoV-2 between 1 February 2020 and 1 March 2021. Clinical, laboratory and radiology findingswere obtained. Treatment regimens and patient outcome data were obtained by reviewing the electronic medical record. Mean age was 49.9 (22–68) years, and twelve (67%) patients were male. The most common symptoms were fever (n = 9, 50%), nausea/vomiting (n = 7, 39%), cough (n = 6, 33%), dyspnea (n = 6, 33%) and fatigue (n = 6, 33%). Headache was reported by five patients (28%). The most notable laboratory findings were elevated levels of C-reactive protein (CRP) and lactate dehydrogenase (LDH). Computed Tomography (CT) of the chest was performed in all hospitalized patients (n = 11, 7%), and showed ground-glass opacities (GGO) in 11 patients (100%), of whom nine (82%) had GGO combined with pulmonary consolidations. Six (33%) patients received remdesivir, five (28%) intravenous dexamethasone either alone or in combination with remdesivir, and 15 (83%) were treated with broad spectrum antibiotics including co-amoxicillin, tazobactam-piperacillin and meropenem. Four (22%) patients were transferred to the intensive care unit, two patients (11%) required invasive mechanical ventilation who could not be successfully extubated and died. Eighty-nine percent of our patients survived COVID-19 and were cured. Two patients with severe COVID-19 did not survive.